Memonitor Hidroponik Dengan Sistem Wick Berbasis Internet Of Things (IoT) Menggunakan Mikrokontroler Dengan Metode Fuzzy Logic - Furqhan Chaesar Mandala Putra; Farid Thalib (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2023)
Hydroponics is one of the innovations in the food system that does not use soil but uses water elements and other mediums. The hydroponic farming system can help in farming activities, one of the hydroponic methods that is easy to apply is the wick system, but it requires attention and time to be able to carry out a hydroponic planting system. Along with the development of technology, innovations have emerged for hydroponic cultivators to carry out remote monitoring through the concept of the Internet of Things (IoT) with tools that will work automatically in measuring the pH of water and the water level of hydroponic plants of the wick system. The automated system uses the fuzzy logic method as data processing and ESP32 as the microcontroller. To avoid misreading the value of the pH sensor and water level sensor, the calculation of the average equation, comparison, and presentation of errors is used in the sensor data readings. The test results showed that the design tool in monitoring hydroponic plants of the wick system was able to maintain the normal value of water pH, maintain the stability of the water level and identify errors in the reading of the sensor data value. With this research, it is hoped that the application of IoT and the Fuzzy Logic method can become literature in the integration of the development of wick method hydroponic systems in order to maximize yields and reduce the risk of plant errors and failures.